2000
DOI: 10.1111/j.1749-6632.2000.tb05380.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of the Baroreceptor Reflex after Bacterial Endotoxin

Abstract: A BSTRACT : Lipopolysaccharide (LPS), an endotoxin that elicits the production of several cytokines, induces cardiovascular changes characterized by increased perfusion of immune organs and compensatory sympathetic vasoconstriction in other tissues. We therefore hypothesized that to adapt to altered blood flow distribution following LPS administration, changes in the sensitivity of reflexes that control blood pressure would occur. Our data show that the sensitivity of the baroreceptor reflex increases signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In contrast, the net blood pressure increase in response to infusion of the ␣ 1 -agonist phenylephrine was not altered, indicating that the (peripheral) vascular responsiveness to ␣-adrenergic stimulation was well preserved. This is in accordance with previous observations in rodents (27).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, the net blood pressure increase in response to infusion of the ␣ 1 -agonist phenylephrine was not altered, indicating that the (peripheral) vascular responsiveness to ␣-adrenergic stimulation was well preserved. This is in accordance with previous observations in rodents (27).…”
Section: Discussionsupporting
confidence: 94%
“…Four, previous studies on the baroreflex function during infusion of bacterial endotoxins had limitations that were avoided in the present study (8,32). A most important limitation was that in previous studies baroreceptors were stimulated and unloaded by vasoactive drug administration.…”
Section: Discussionmentioning
confidence: 87%
“…Gupta and Sharma [71] have also demonstrated that the fall in blood pressure, which occurs 2 h after LPS injection, is associated with an increase in aortic iNOS and eNOS protein expression, and systemic and tissue nitrate+nitrite (NO X ) levels. Compensatory mechanisms, including activation of renin-angiotensin-aldosteron system, increased sensitivity of baroreceptor reflex mechanisms, and increased production of endothelin-1 and cathecolamines, which are known to activate phospholipase A 2 and release arachidonic acid from tissue lipids, and results in prostaglandin synthesis, and also stimulate production of reactive nitrogen and oxygen species, have also been reported to be responsible for the changes in the formation of vasoregulatory molecules that could contribute to the fall in blood pressure during the early phase of LPS-induced endotoxemia [6776]. Therefore, the vasodilator prostaglandins and NO could cause a decrease in blood pressure which is followed by increased expression of COX-2 and iNOS and decreased expression of CYP4A, resulting in sustained decrease in blood pressure.…”
Section: Discussionmentioning
confidence: 99%